Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b)x3-2x2-4xy2+x
=x(x2-2x-4y2+1)
=x[(x2-2x+1)-4y2]
=x[(x-1)2-4y2]
=x(x-1-2y)(x-1+2y)
c) (x+2)(x+3)(x+4)(x+5)-8
=[(x+2)(x+5)][(x+3)(x+4)]-8
=(x2+5x+2x+10)(x2+4x+3x+12)-8
=(x2+7x+10)(x2+7x+12)-8
đặt x2+7x+10 =a ta có
a(a+2)-8
=a2+2a-8
=a2+4a-2a-8
=(a2+4a)-(2a+8)
=a(a+4)-2(a+4)
=(a+4)(a-2)
thay a=x2+7x+10 ta đc
(x2+7x+10+4)(x2+7x+10-2)
=(x2+7x+14)(x2+7x+8)
bài 2 x3-x2y+3x-3y
=(x3-x2y)+(3x-3y)
=x2(x-y)+3(x-y)
=(x-y)(x2+3)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4+x^3+x^2-1\)
\(=x^3\left(x+1\right)+\left(x^2-1\right)\)
\(=x^3\left(x+1\right)+\left(x-1\right)\left(x+1\right)\)
\(=\left(x^3+x-1\right)\left(x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
a: \(\Leftrightarrow4x^2=9\)
=>(2x-3)(2x+3)=0
hay \(x\in\left\{\dfrac{3}{2};-\dfrac{3}{2}\right\}\)
b: \(\Leftrightarrow4x^2-4x+1-4x^2+12x-x+3=-3\)
\(\Leftrightarrow7x+4=-3\)
hay x=-1
Bài 3:
x=2013
nên x+1=2014
\(A=x^4-x^3\left(x+1\right)+x^2\left(x+1\right)-x\left(x+1\right)+2014\)
\(=x^4-x^4-x^3+x^3+x^2-x^2-x+2014\)
=2014-x
=2014-2013=1
![](https://rs.olm.vn/images/avt/0.png?1311)
(3x-1)^2 - 16 = (3x-1)^2 - 4^2
= (3x-1-4)(3x-1+4)
= (3x-5)(3x+3)
\(\left(3x-1\right)^2-16\)
\(=\left(3x-1\right)^2-4^2\)
\(=\left(3x-1-4\right)\left(3x-1+4\right)\)
\(=\left(3x-5\right)\left(3x+3\right)\)
\(=3\left(x+1\right)\left(3x-5\right)\)
a) \(x^2+x=0\)
\(\Rightarrow x.\left(x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=-1\end{cases}}\)
b) \(x^2-5x=0\)
\(\Rightarrow x.\left(x-5\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x-5=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=5\end{cases}}\)
c) \(x.\left(x-2\right)+x-2=0\)
\(\Rightarrow x.\left(x-2\right)+\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right).\left(x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
d) \(x.\left(x-3\right)-x+3=0\)
\(\Rightarrow x.\left(x-3\right)-\left(x-3\right)=0\)
\(\Rightarrow\left(x-1\right).\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\x-3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=1\\x=3\end{cases}}\)
e) \(x^2-4=0\)
\(\Rightarrow x^2=4\)
\(\Rightarrow x=\pm2\)